Effectiveness of Using Technological Pedagogical and Content Knowledge (TPACK)-Based Digital Functional Nahwu Material - Salma, Kunti Nadiyah; Hasanah, Mamluatul; Muassomah, Muassomah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research is urgent because Nahwu is one of the basics of learning Arabic, especially for everyday communication. As time goes by, it has been developed by utilizing TPACK-based technology. The research aims to determine the effectiveness of digital Functional Nahwu material developed based on TPACK at MAN Pacitan. This research uses a quantitative approach with a population of all class X MAN Pacitan totaling 352 students. The sampling technique was purposive, so the samples were taken from class X.1 with 35 students and class X.4 with 35 students of MAN Pacitan. Data collection techniques used tests and questionnaires. The analysis uses an independent sample t-test. The research results are the independent sample t-test with SPSS, obtained Sig results. (2-tailed) 0.000 so that it is smaller than 0.05, then Ho is rejected, and Ha is accepted. This means that the TPACK-based digital functional Nahwu material is effectively used in Nahwu learning in class X.4 MAN Pacitan.